2018
DOI: 10.1177/2045894018775056
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in chronic lung diseases: comparison to other pulmonary hypertension groups

Abstract: Group 3 pulmonary hypertension (PH) is a common complication of advanced chronic lung disease. Our hypothesis was that group 3 PH is associated with a more severe baseline presentation and a more severe prognosis compared to group 1 pulmonary arterial hypertension (PAH), chronic thromboembolic PH (group 4), and group 5 PH. We retrospectively analyzed consecutive incident PH patients in a single center between January 2006 and November 2014. Data were acquired from a prospective database. Clinical, functional, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 39 publications
(59 reference statements)
1
35
0
Order By: Relevance
“…We decided to use TLC/DLCO ratio as the assessment of TLC is the best test to correctly differentiate restrictive from normal lung function. The reduction of TLC is a stronger risk factor for mortality than FVC in an unselected population of elderly patients [28], and it was associated with mortality among patients with group 3 PH [27]. 6MWT results showed significantly longer distance in group A compared to group B (583 vs 478 m, respectively).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We decided to use TLC/DLCO ratio as the assessment of TLC is the best test to correctly differentiate restrictive from normal lung function. The reduction of TLC is a stronger risk factor for mortality than FVC in an unselected population of elderly patients [28], and it was associated with mortality among patients with group 3 PH [27]. 6MWT results showed significantly longer distance in group A compared to group B (583 vs 478 m, respectively).…”
Section: Discussionmentioning
confidence: 92%
“…It was found that only about 60% of those with a restrictive spirometric pattern defined as FVC < 80% predicted and FEV 1 /FVC > 0.7 before bronchodilatation, have a true restrictive impairment of lung function defined as a TLC below the lower limit of normal [26]. In addition, TLC has been shown to be significantly associated with mortality in patients with group 3 PH [27] and in an unselected population of elderly patients [28].…”
Section: Introductionmentioning
confidence: 99%
“…According to WHO, COPD patients with PH are categorized as Group 3 PH. Group 3 PH patients have a significantly lower survival rate in comparison with PH patients without COPD (Group 1), followed by Group 4 (patients with chronic thromboembolic PH) and Group 5 (patients with hematologic disorders, systemic disorders, and metabolic disorders) (36). A population-based study reported that a higher proportion of older males (aged more than 70 years) are prone to PH with COPD.…”
Section: Causal Role Of Ph For Right Ventricular Failure In Patients With Copdmentioning
confidence: 99%
“…The threshold to define PH in lung disease has been lowered [ 1 ] to define mild-moderate PH as mean pulmonary artery pressure (mPAP) ≥21 mmHg in the presence of increased pulmonary vascular resistance (PVR ≥3 wood units, WU) or mPAP ≥25 mmHg, and severe PH as mPAP ≥35 mmHg or mPAP ≥25 mmHg with cardiac index (CI) <2 L/min/m 2 . PH is usually mild to moderate in COPD but is severe in 1–5% of cases [ 8 , 11 ], representing a distinct subgroup with markedly worse prognosis and predominant vascular impairment associated with relatively mild obstructive disease [ 6 , 12 ], which has been described as a ’pulmonary vascular phenotype’ (PVP) [ 13 ]. A paradigm shift is taking place in PH research, aimed at the analysis of phenotypic heterogeneity and ultimately precision medicine [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%